Identifikasi Tumbuhan Lumut di Kawasan Wisata Gunung Galunggung Kabupaten Tasikmalaya Jawa Barat - Putra, Rinaldi Rizal; Hernawati, Diana; Fitriani, Rita (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
Galunggung mountain tourism spot is one of the natural tourism objects in Tasikmalaya regency possessing high biodiversity of living things, notably moss. The well-preserved environmental conditions in the area of Galunggung mountain enable the moss to grow luxuriantly and has miscellaneous varieties. This study aimed at identifying the moss living in around Galunggung mountain, Tasikmalaya. It was conducted on November 2017 through descriptive exploratory method with survey technique. The data were analysed descriptively by collecting specimens of the moss discovered in each observing station. The observing locations were situated in three different locations (stations) based on hierarchical height levels. Based on the identification, the moss proliferating in Galunggung mountain were classified into 20 species. The moss species dominantly identified in the entire observing stations were Bryum billardierii, Acroporium sp., Leucobryum sp., Marchantia polymorpha, and Calymperes sp. Â Â